Rancang Bangun Perangkat Akuisisi Data Gas Emisi Karbon Monoksida Pada Kendaraan Sepeda Motor - Saputra, Irwan; Arief Kusuma, Hollanda; Suhendra, Tonny (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2023)
Exhaust emissions can cause air pollution. Carbon monoxide is one of the air pollution comes from motor vehicle gas emissions. From current technological developments, low-cost gas sensors have been widely used. In research, data acquisition devices have been successfully developed using the MQ-7 sensor, ESP32, micro SD card, TFT display, and keypad. The results of the sensor calibration get 10 motorcycle data with a coefficient of determination (R2) of 0.9273 with a percentage of 92.73%. The average accuracy of the MQ-7 sensor is 91.23% with an error percentage of 1.82% and an RMSE of 0.379. From the results of the sensor calibration, it can be seen that the MQ-7 sensor has a fairly good level of accuracy. From field test, 30 motorcycles has been test. From the results of the field test of 30 motorcycles, factors that affect the value of carbon monoxide gas in motorcycles include dirty air filters, fuel used, and motorbike maintenance. As for the year of the vehicle does not affect the value of carbon monoxide gas.